Changes in Occurrence of Diarrheal and Respiratory Diseases before and during COVID-19 Pandemic among Nepalese Population - Maheshor Kaphle; Anil Paudel; Laxmi Adhikari; Pratibha Shrestha; Santosh Khadka; Rajesh Karki (Journal of Karnali Academy of Health Sciences, 2023)
Background: The government of Nepal has adopted a number of preventative and control measures to halt the spread of coronavirus disease (COVID-19). In this study, we aimed to determine whether the use of preventive and control measures such as hand washing, social distancing, lockdown implementation, and mask-wearing has significantly slowed down the spread of infectious diseases like diarrhoea and respiratory illnesses during the pandemic period.